Rapport (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
The deprivation of liberty of minors in conflict with the law in Burkina Faso. The author describes the different phases in which children may be deprived of their liberty: the preliminary investigation phase, the investigation phase, the trial phase and the enforcement of detention decisions.
Keywords: Mediation; Reconciliation; Justice; Punishment; Children; Juvenile detention; Juvenile delinquency; Deprivation of Liberty; Preliminary Investigation; Investigation Phase; Enforcement of Decisions